Thrombectomy versus Medical Management in Mild Strokes due to Large Vessel Occlusion: Exploratory Analysis from the EXTEND‐IA Trials and a Pooled International Cohort. Issue 3 (25th July 2022) - Sarraj, Amrou; Albers, Gregory W.; Blasco, Jordi; Arenillas, Juan F.; Ribo, Marc; Hassan, Ameer E.; de la Ossa, Natalia Pérez; Wu, Teddy Yuan‐Hao; Cardona Portela, Pere; Abraham, Michael G.; Chen, Michael; Maali, Laith; et al.
Abstract : Objective: This study was undertaken to evaluate functional and safety outcomes for endovascular thrombectomy (EVT) versus medical management (MM) in patients with large vessel occlusion (LVO) and mild neurological deficits, stratified by perfusion imaging mismatch. Methods: The pooled cohort consisted of patients with National Institutes of Health Stroke Scale (NIHSS) < 6 and internal carotid artery (ICA), M1, or M2 occlusions from the Extending the Time for Thrombolysis in Emergecy Neurological Deficits ‐ Intra‐Arterial (EXTEND‐IA) Trial,   Tenecteplase vs Alteplase before Endovascular Thrombectomy in Ischemic Stroke (EXTEND‐IA TNK) trials Part I/II and prospective data from 15 EVT centers from October 2010 to April 2020. RAPID software estimated ischemic core and mismatch. Patients receiving primary EVT (EVTpri ) were compared to those who received primary MM (MMpri ), including those who deteriorated and received rescue EVT, in overall and propensity score (PS)‐matched cohorts. Patients were stratified by target mismatch (mismatch ratio ≥ 1.8 and mismatch volume ≥ 15ml). Primary outcome was functional independence (90‐day modified Rankin Scale = 0–2). Secondary outcomes included safety (symptomatic intracerebral hemorrhage [sICH], neurological worsening, and mortality). Results: Of 540 patients, 286 (53%) received EVTpri and demonstrated larger critically hypoperfused tissue (Tmax > 6 seconds) volumes (median [IQR]: 64 [26–96] ml vs MMpri : 40 [14–76] ml, p  < 0.001) and higher presentation NIHSS (median [IQR]: 4 [2–5] vs MMpri : 3 [2–4], p  < 0.001). Functional independence was similar (EVTpri : 77.4% vs MMpri : 75.6%, adjusted odds ratio [aOR] = 1.29, 95% confidence interval [CI] = 0.82–2.03, p  = 0.27). EVT had worse safety regarding sICH (EVTpri : 16.3% vs MMpri : 1.3%, p  < 0.001) and neurological worsening (EVTpri : 19.6% vs MMpri : 6.7%, p  < 0.001). In 414 subjects (76.7%) with target mismatch, EVT was associated with improved functional independence (EVTpri : 77.4% vs MMpri : 72.7%, aOR = 1.68, 95% CI = 1.01–2.81, p  = 0.048), whereas there was a trend toward less favorable outcomes with primary EVT (EVTpri : 77.4% vs MMpri : 83.3%, aOR = 0.39, 95% CI = 0.12–1.34, p  = 0.13) without target mismatch ( p interaction  = 0.06). Similar findings were observed in a propensity score‐matched subpopulation. Interpretation: Overall, EVT was not associated with improved clinical outcomes in mild strokes due to LVO, and sICH was increased. However, in patients with target mismatch profile, EVT was associated with increased functional independence. Perfusion imaging may be helpful to select mild stroke patients for EVT. ANN NEUROL 2022;92:364–378